Resisting/existing: Assemblage as a Strategy of Resistance in the palabrarmas of Cecilia Vicuña - Macchiavello, Carla María (Universidad de Chile. Facultad de Filosofía y Humanidades, 2017)
This essay is based on the poetic-visual production developed by Cecilia Vicuña in Colombia between 1975 and 1980 through the concept palabrarmas (words-weapons), which is understood as an assemblage and an ecological endeavor. After the coup d’état in Chile, Vicuña developed the concept palabrarmas as a way of exploring language, arming oneself with it, and re-configuring reality. Palabrarmas is a poetic practice and a process that invites us to pay attention to the relationships of interdependence and connection that conform the world, becoming aware of the creative (and destructive) capacities of those who inhabit it. Through the analysis of Vicuña’s visual poetry and the film What is Poetry to You?, two areas that have not been dealt with in the analysis of Vicuña’s work, this essay argues that the concept palabrarmas not only expands the concept of poetry and its relationship with visual arts including other disciplines like documentary cinema, but it is also useful as a strategy of social resistance.